H∞ Consistency of T-S Fuzzy Supply Chain System Based on Trust Mechanism - Yong Huang; Qingkui Li (Applied Sciences)
As the market environment becomes increasingly complex, the demands for supply chain performance and security are continuously rising. Consequently, it is crucial to consider the role of trust factors within the system. This paper introduces a trust mechanism in the interaction between supply and demand within supply chain logistics and information flow. The supply chain system, characterized by varying degrees of trust, is modeled as multiple subsystems using the T-S fuzzy model. The challenge of mitigating the bullwhip effect, which refers to the amplification of demand variability within the supply chain, is reformulated as an <semantics>H∞</semantics> consistency problem. A productivity and distributed consistency protocol switching controller based on fuzzy rules is designed, providing sufficient conditions for the entire system to achieve consistency. The proposed method effectively suppresses the bullwhip effect and allows certain nodes in the system to be temporarily in an abnormal state. Finally, the method’s effectiveness is validated through simulation examples.